Altered Metabolic Phenotype of Immune Cells in a Spontaneous Autoimmune Uveitis Model - Barfüßer, Claudia; Wiedemann, Carmen; Hoffmann, Anne L. C.; Hirmer, Sieglinde; Deeg, Cornelia A. (Frontiers in Immunology, 2021)
As one of the leading causes of blindness worldwide, uveitis is an important disease. The exact pathogenesis of autoimmune uveitis is not entirely elucidated to date. Equine recurrent uveitis (ERU) represents the only spontaneous animal model for autoimmune uveitis in humans. As the metabolism of immune cells is an emerging field in research and gains more and more significance to take part in the pathogenesis of various diseases, we conducted experiments to investigate the metabolism of immune cells of ERU cases and healthy controls. To our knowledge, the link between a deviant immunometabolism and the pathogenesis of autoimmune uveitis was not investigated so far. We showed that PBMC of ERU cases had a more active metabolic phenotype in basal state by upregulating both the oxidative phosphorylation and the glycolytic pathway. We further revealed an increased compensatory glycolytic rate of PBMC and CD4+ T cells of ERU cases under mitochondrial stress conditions. These findings are in line with metabolic alterations of immune cells in other autoimmune diseases and basic research, where it was shown that activated immune cells have an increased need of energy and molecule demand for their effector function. We demonstrated a clear difference in the metabolic phenotypes of PBMC and, more specifically, CD4+ T cells of ERU cases and controls. These findings are another important step in understanding the pathogenesis of ERU and figuratively, human autoimmune uveitis.